1985
DOI: 10.1002/cyto.990060406
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric fluorescence emission spectrum analysis of hoechst‐33342‐stained DNA in chicken thymocytes

Abstract: Hoechst-33342-stained chicken thymocytes were analysed simultaneously on two fluorescence wavelength bands (green and violet) in our custom-built flow cytometer, and two major subsets were identified. In one subset (33% of the total) the emission spectrum remained constant with time, with little change in the respective green and violet fluorescence intensities. In the other subset (42% of the total) the green fluorescence increased during staining, resulting in a considerable change in the green-to-violet rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 12 publications
2
30
1
Order By: Relevance
“…An identical DNA index (DI) of the second G0/G1 peak (B) was obtained with both DRAQ5 and PI staining. (3,16). However, this fluorescent dye requires UV excitation (16), and thus is not ideal for use in most commercial clinical instruments.…”
Section: Discussionmentioning
confidence: 99%
“…An identical DNA index (DI) of the second G0/G1 peak (B) was obtained with both DRAQ5 and PI staining. (3,16). However, this fluorescent dye requires UV excitation (16), and thus is not ideal for use in most commercial clinical instruments.…”
Section: Discussionmentioning
confidence: 99%
“…These dyes are UV-excitable with excitation/emission maxima at 350/460 nm. Additionally their fluorescence emissions undergo a subtle violet-to-red shift as DNA binding proceeds (13,14). The spectral shift suggests multiple binding modes dependent on dye:base-pair ratios.…”
mentioning
confidence: 99%
“…The nature of this shift appears to be due to the chromatin microenvironment. 5,10,12 In this study we observed that cells arrested in different phases of the cell cycle, stained with the vital fluorescent dye Heochst 33342 and analyzed with the PARISS HSI system, demonstrated unique, cell cycle dependent spectral signatures.…”
Section: Discussionmentioning
confidence: 76%
“…7,8,9 It has been shown that subtle changes in the chromatic qualities of cell permeant fluorescent dyes targeting these cellular components occur. 5,6,10,11,12 We hypothesize that these changes could be quantified, and unique spectral signatures could be generated representing the cell cycle status of live cells in culture.…”
Section: Introductionmentioning
confidence: 99%